2014
DOI: 10.1021/am406026n
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive and Low Cost Ni-PET Flexible Substrate for Efficient Dye-Sensitized Solar Cells

Abstract: The highly conductive and flexible nickel-polyethylene terephthalate (Ni-PET) substrate was prepared by a facile way including electrodeposition and hot-press transferring. The effectiveness was demonstrated in the counter electrode of dye-sensitized solar cells (DSSCs). The Ni film electrodeposition mechanism, microstructure, and DSSC performance for the Ni-PET flexible substrate were investigated. The uniform and continuous Ni film was first fabricated by electroplating metallic Ni on fluorine-doped tin oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In anodic part of voltammograms, the anodic peak is clearly observed, however in cathodic part, the cathodic peak is not observed and the absolute value of cathodic current density increases continuously with increasing overpotential. The absence of cathodic peak in voltammograms, corresponding to electrochemical deposition of Ni on other semiconductor substrates, was reported in previous works [14,[22][23][24][25]. One reason of this observation might be the side reduction of H + ions at high negative potentials [5,14].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In anodic part of voltammograms, the anodic peak is clearly observed, however in cathodic part, the cathodic peak is not observed and the absolute value of cathodic current density increases continuously with increasing overpotential. The absence of cathodic peak in voltammograms, corresponding to electrochemical deposition of Ni on other semiconductor substrates, was reported in previous works [14,[22][23][24][25]. One reason of this observation might be the side reduction of H + ions at high negative potentials [5,14].…”
Section: Introductionmentioning
confidence: 57%
“…In addition, scanning electron microscopy (SEM) and x-ray diffraction (XRD) methods were used for morphological analysis and phase identification, respectively. semiconductor substrates has been reported in literature [5,10,11,22,24]. In anodic part of voltammograms, the anodic peak is clearly observed, however in cathodic part, the cathodic peak is not observed and the absolute value of cathodic current density increases continuously with increasing overpotential.…”
Section: Introductionmentioning
confidence: 77%
“…[ 2 ] The typical supporting substrate for such printed devices is polyethylene teraphthalate (PET), a low‐cost, transparent polymer with a practical upper processing temperature limit of 150 °C. [ 3,4 ] Its use necessitates low‐temperature processing of all the layers within the completed PSC devices. While hybrid lead halide perovskites are inherently amendable to these temperature limits, complying with these for the other layers within a PSC remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is highly important to replace Pt with alternative materials without the sacrice of decreasing activity and stability in comparison to Pt-based catalysts. [23][24][25] Thus, the nickel phosphides with tailored conguration have become an important issue for the success of the counter electrode. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Among these Pt-free catalysts, nickel phosphides have become a focus of interest because of their magnetic and mechanical resistance properties, and good corrosion and wear resistances.…”
Section: Introductionmentioning
confidence: 99%
“…22 As a catalyst material in counter electrode, large surface area, high electrical conductivity, and an open porous structure are required for fast transport of electrolyte and electron. [23][24][25] Thus, the nickel phosphides with tailored conguration have become an important issue for the success of the counter electrode. It has been reported that Ni 5 P 4 exhibits a decent catalytic activity for the iodide/triiodide redox couple and the catalytic activity can be improved signicantly when Ni 5 P 4 and mesoporous carbon are combined into one composite (Ni 5 P 4 /C) due to the reduced charge-transfer resistance and diffusion impedance.…”
Section: Introductionmentioning
confidence: 99%